PENGARUH PENGGUNAAN LAHAN PERKEBUNAN KALAPA SAWIT TERHADAP LINGKUNGAN SOSIAL EKONOMI MASYARAKAT DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - , ANDI ZULFITRI, S. T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research location is in Petapahan Sub-district, Kuantan Singingi District, Riau Province. The purpose of this research is to examine the conditions around oil palm plantations due to used land for oil palm plantations in the abiotic environment, biotic environment and assess the effect of the use of land for oil palm plantations on the socio-economic environment in the study area as well as provide an alternative environmental management strategies that are appropriate for minimize the damage. This study used a survey method. This type of survey method used in this research is a survey method field. The data collected is the primary data and secondary data. Primary data is data obtained from observations in the field, the questionnaire and interviews with residents who live on site research. Kuantan Singingi district forest area in 1994 418.800 ha to 276.700 ha in 2000, shows there has been a shrinkage of forest area of 142 100 ha within 6 years or a everage change is 23 683 ha / year. Environmental damage that occurred in Kuantan Singingi district usually occur due to the use of land into oil palm plantations by the private sector and by the public. Factors that cause environmental damage caused by the use of forest land into oil palm plantations